Análise de concentração e poder de mercado no segmento de acesso à internet banda larga fixa no Brasil no período de 2010 a 2020 - Alves, Francisco Weber (2021)
The rising wave of technological innovations in the telecommunicatons sector in Brazil in the last decade has impacted the market structure on access to fixed broadband internet. The main goal of this study is to calculate the concentration and Market power indexes to assess the evolution of the fixed broadband internet in Brazil and in the Northeast Region, by using the database of active accesses presented by Anatel regarding to informations provided by the operators between 2010 and 2020. The focus of this research is the analysis of the expansion of small providers (PPP) and its impact on the dynamics of Market competition. In the end of 2020, small providers have achieved the market leadership with 41.3% (Brazil) and 61.5% (Northeast), by reaching the demand of the segment. Herfindahl-Hirschman Index (HHI) in Brazil (1.255) and Northeast (683) testified “Non-concentrated market”. To test that hypothesis of concentration, it was used the concentration indexes found in the economic literature – Market Share, Concentration Ratio and Herfindahl-Hirschman Index (HHI). It was also performed couterfactual analysis with three hypothesis to test the anticompetitive effects after the acquisition of the operator OI SA by the three biggest companies of the Market – CLARO, VIVO and TIM. All of the scenarios in Brazil showed increase in the Market concentration, which was classified as Moderately. Without concern, therefore, the sales operation might be approved by CADE, no restrictions.